[tex]x:7=11,r\ \textgreater \ 0 \\ =\ \textgreater \ r=1,2,3,4,5,6. \\ =\ \textgreater \ x:7=11.rest.1 \\ =\ \textgreater \ x=11*7+1 \\ =\ \textgreater \ x=77+1 \\ =\ \textgreater \ 78 \\ \\ x:7=11.rest.2 \\ =\ \textgreater \ x=11*7+2 \\ =\ \textgreater \ x=79 \\ \\ x:7=11.rest.3 \\ =\ \textgreater \ x=11*7+3 \\ =\ \textgreater \ x=80 \\ \\ x:7=11.rest.4 \\ =\ \textgreater \ x=11*7+4 \\ =\ \textgreater \ 81 \\ \\ x:7=11.rest.5 \\ =\ \textgreater \ x=11*7+5 \\ =\ \textgreater \ 82 \\ \\ x:7=11.rest.6 \\ =\ \textgreater \ x=11*7+6 \\ =\ \textgreater \ x=83 \\ \\ Sper \\ ca \\ te-am \\ ajutat![/tex]